Tegami bachi, Letter Bee. Volume 2, The letter to Jiggy Pepper - Asada, Hiroyuki, 1968- (Viz Media, 2010)
In a land of perpetual night, your heart is your light. Lag is close to becoming a Letter Bee! On the way to his final interview at the National Postal Service, he found a dingo: Niche, a feral young girl with shocking strength and hair made of golden swords. Now, as they approach the bridge to the middle-caste district, they stop to rest in Kyrie, a desperado town. They meet Nelli, a friendly young man who shows them to an inn. Nelli's so helpful that neither Lag nor Niche notice him steal Lag's Crossing Pass!